An exploratory look into the increasing visibility of queer-themed content: Dhaka-based, youth-dominated social media platforms - Hassan, Mashaekh (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Social Science in Anthropology, 2022.